A consistency analysis between the distinctive development of various ethnic groups and the construction of the Chinese national community - Hongpeng, Kang; Yok Fee, Lee; Ku Samsu, Ku Hasnita; Ismail, Mohd. Mahadee (Human Resources Management Academic Research Society (HRMARS), 2024)
The ethnic groups in China possess distinct uniqueness; on one hand, each ethnic group has its own unique ethnic culture. On the other hand, all ethnic groups share common cultural characteristics, which also form the basis of the Chinese nation. With the development of society, whether the national unity of the Chinese nation is consistent with the unique development of each ethnic group is an important direction of current research. This article analyzes the compositional characteristics of the Chinese nation, and on this basis, studies the consistent relationship between the 56 ethnic groups that constitute the Chinese nation and the Chinese nation community. Through the analysis of literature and secondary data, this article found that the structural characteristics of the Chinese nation reflect its ethnic relations. In modern China, the distinctive development of each ethnic group is consistent with, and even promotes, the construction of the Chinese national community. The significance of this article lies in analyzing the consistency between the distinctive development of various ethnic groups and the construction of the Chinese national community through historical documents and empirical data, providing a reference perspective for promoting national unity and strengthening the construction of the Chinese